PENGARUH KEBIJAKAN DEVIDEN, STRUKTUR KEPEMILIKAN DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN - Tiya Nur Pratiwi; Edwin Agus Buniarto; Mawar Ratih Kusumawardani; Ahmad Jamaludin Sahlan (Commodities, Journal of Economic and Business, 2022)
This study aims to examine the effect of devidend policy, ownership strucktur and growth opportunity to firm value on insurance company listed on capital market indonesia in 2012-2016. Variabel in this study is devidend policy represented by devidend payout ratio, ownership strucktur represented by manajerial ownership and growth opportunity represented by asset growth then firm value represented by price book value. This study is a type of quantitative research. The population in this study are 14 insurance companies listed on sahamok.com, the sample in this study chosen by purposive sampling method and obtained 6 compaanies according to the criteria established, so there are 30 financial statement are processed. This study using multiple regression analysis,t analysis, f analysis. The result this study show that variables devidend policy, ownership strucktur and growth opportunity have significant effect to firm value. Then variabel devidendd policy, ownership strucktur and growth opportunity jointly have influence to firm value.